198k views
5 votes
Solve : 3X + 3x + 1 + 3x + 2 = 39​

User Tuor
by
5.5k points

2 Answers

1 vote

Answer:

x = 4

Explanation:

combine all of the 3x first to get:

9x + 1 + 2 = 39

9x + 3 = 39

subtract 3 from both sides:

9x = 36

divide by 9

x = 4

User Andreas F
by
5.1k points
4 votes

Explanation:


3x + 3x + 1 + 3x + 2 = 39 \\ 9x + 3 = 39 \\ 9x = 39 - 3 \\ 9x = 36 \\ x = (36)/(9) \\ x = 4

User Dave Lillethun
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.